MOMEN HISTORY PENYINGKIRAN ‘MASYARAKAT ADAT’ DI SULAWESI TENGAH - Ferry Rangi (DIALEKTIKA, 2021)
This article is to describe how colonial power, military unrest at the start of independence, national and international development agendas have excluded the 'indigenous peoples' of their ancestral land in Central Sulawesi. Through the ethnographic method reveals the historical moments of the exclusion. And to see the weakness of the concept of 'indigenous people' that has been used so far to fight for their rights. Key words: Indigenous people, development, agenda, climate change